Thermoelectric properties of Bi2Te3/Sb2Te3 thin films - Gonçalves, L. M. (2006)
The deposition and characterization of n-type Bi2Te3 and p-type Sb2Te3 semiconductor films are reported. The films were deposited by thermal co-evaporation on a 25 µm thick polyimide (kapton) substrate. The co-evaporation method is inexpensive, simple, and reliable, when compared to other techniques that need longer time periods to prepare the starting material or require more complicated and expensive deposition equipment. Seebeck coefficients of -189 µVK-1 and +140 µVK-1 and electrical resistivities of 7.7 µΩm and 15.1 µΩm were measured at room temperature on n-type and p-type films, respectively. These values are better than those reported for films deposited by co-sputtering or electrochemical deposition, and are close to those reported for films deposited by metal-organic chemical vapour deposition or flash evaporation. Because of their high figures of merit, these films will be used for the fabrication of a micro-Peltier element, useful in temperature control and laser-cooling for telecommunications.